PERAN GOOD CORPORATE GOVERNANCE (GCG) DALAM MEMODERASI PENGARUH CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP CORPORATE PERFORMANCE - Dinaraty Alya Putri, (2022)
This research is using quantitative study aimed to see whether there are the role of Good Corporate Governance (GCG) in moderating the influence of Corporate Social Responsibility (CSR) on Corporate Performance. This study uses non-financial SOEs for the 2018-2020 period found on the official website of the Ministry of SOEs as samples. The sample selection was done by purposive sampling technique so that the number of samples that could be used was 32 companies multiplied by three periods, namely 96 observations. Hypothesis testing in this study uses Simple Linear Regression Analysis with STATA program and a significance level of 5% (0.05). The results of the test are (1) there is no significant effect of CSR on Corporate Performance, (2) GCG cannot strengthen the influence of CSR on Corporate Performance. Keywords : CSR, GCG, and Corporate Performance.